Characteristic of Yield, FFA, Impurity Content, Water Content and pH In High Acid CPO (HACPO) - Reynaldo Reynaldo; Yazid Ismi Intara; Bosman Sidebang (UNIVED Press, Dehasen University Bengkulu, 2026)
Purpose : This study aims to obtain the results of the analysis of the characteristics of high acid CPO. Methodology: Measurement of HACPO oil yield values ​​is obtained from the percentage of HACPO oil produced per unit weight of palm fruit flesh. Quality testing of free fatty acid (FFA) levels, impurities and water content and pH measurements. Results: The results show that the HACPO oil yield produced in the study ranged from 19.24% - 19.66%, indicating lower than the CPO yield study. HACPO quality analysis showed higher values ​​of impurities and water content (> 5%) Apart from that, there was an increase in the levels of free fatty acids along with the longer storage time of HACPO, namely from day 1 at 7.30% to day 7 at 7.61% with pH measurements in the range of pH at 4.19-4.38 on the 7th day, the pH tends to be lower (acidic) compared to the previous day's storage treatment. Findings: The HACPO quality shows results that do not meet the standards of SNI 01-2901-2006 for food CPO, possibly still uses simple and semi-manual machines during the second boiling and storage techniques. Originality: research on the yield and quality of HACPO from the processing industry by the community has not been published. Type of paper: papper research was laboratory-scale experimental study on the yield and quality of HACPO